The Implementation of Quiz-Demonstration-Practice-Revision (QDPR) Learning Model to Improve University Studentsâ€™ Knowledge of English Pronunciation and Their Ability to Pronounce English Central Vowel /á´§/ and English Back Vowel /Î±Ë/ - Raihun Adaniyah (VELES Voices of English Language Education Society, 2017)
The study aimed at knowing the significant contribution of Quiz-Demonstration-Practice-Revision (QDPR) Learning Model to improve University students’ knowledge of English pronunciation and their ability to pronounce English central vowel /ʌ/ and English back vowel /α:/ at Hamzanwadi University. In this study, the present researcher was used Ex-post Facto design and simple random sampling for collecting the data. While the instrument was used by the present researcher: (1) questionnaire., (2) written test for knowledge of English pronunciation., and (3) oral performance for students’ of Hamzanwadi University in ability to pronounce English central vowel /ʌ/ and English back vowel /α:/ to analyzed the data . Whereas, in this study the present researcher was used IBM SPSS 22 for windows. The result of this study was QDPR Learning Model had significant contribution to students’ ability to pronounce English central vowel /ʌ/ and English back vowel /α: / at Hamzanwadi University. Meanwhile, QDPR Learning Model did not contribute to students’ knowledge of English Pronunciation. Finally, QDPR Learning Model is one of the alternative model to teach English pronunciation.